Studies of influence on iron (III) oxide on propagation loss of building materials for 5G wireless communications - Zhong, Yixiao (Nanyang Technological University, 2022)
In this report, the electromagnetic performance of building materials is investigated based on thickness, frequency and volumetric fraction of iron (III) oxide. Mortar samples with different thickness and volumetric fractions are casted and fabricated for the empirical study. S-parameter measurements at 2.4 GHz frequency band, 3.5 GHz mid-band 5G frequency band and 26 GHz high band 5G frequency band are obtained using Vector Network Analyzer in a fully shielded anechoic chamber using free-space method and waveguide method. Transmission coefficients (S21) data are analyzed and compared across different thickness and different volumetric fractions at different frequencies. Our results from the experimental data showed that 2% iron (III) oxide performs the best from the total point of view, and S21 decreases as the thickness and frequency increase. Lastly, the EM characterization of the mortar samples is done by obtaining relative permittivity. An overview of report is summarized with my conclusion and future recommendations.